Ocurrence of Porphyromonas gingivalis in patients with periodontitis in Brazil - Zanini Kantorski, Karla; Rodrigues, Ariana Soares; Zimmemann, Gláucia Santos; Lotufo, Roberto Fraga Moreira (Brazilian Dental Science, 2010)
The aim of this study was to evaluate the occurrence of Porphyromonas gingivalis in patients with periodontitis in Brazil and investigate whether there is a relationship between your occurrence and gender and age. Analysis was performed of 1,386 results of microbiological examinations of samples of subgingival microbiota in patients with periodontitis. Collection was performed by periodontists in private practice and processed by culture in clinical laboratory of oral microbiology. The chi-square test was used to verify the association of occurrence of P. gingivalis with gender and age. It was observed that 59% of examinations were of female patients and 41% were of male patients, most of which aged more than 40 years (64.3%). The occurrence of P. gingivalis was 17.8%. There was no significant difference in the presence of this bacterium in the different age ranges, yet there was a significantly higher occurrence in males. It was observed that, regardless of the age range, the occurrence of P. gingivalis was always significantly higher in males. It was concluded that the occurrence of P. gingivalis in patients with periodontitis in Brazil was 17.8% and was associated with gender, yet had no association with the age range.